Combining finite strain analysis and illite crystallinity to examine strain variation in a shale detachment zone - Rowan L. Hansberry (2019)
© 2019 Determining the physical conditions and material properties of low-grade (sub-green schist facies) deformation accurately is problematic due to the lack of adequate strain indicators and mineral equilibrium assemblages with established relationships to pressure and temperature conditions. For low-grade deformation, proxies such as illite crystallinity are often used to provide broad constraints on these conditions. The relationship between illite crystallinity and temperature remains qualitative, however, it has been suggested that illite crystallinity may be a more appropriate proxy for tectonic strain at low temperatures. Recent work on an exposed shale detachment zone in the Khao Khwang Fold-Thrust Belt has described strain partitioning into shale-dominated “shear domains” which delineate coarser-grained “fault domains”. This strain partitioning is a key influence in the development of the complex three-dimensional shear zone networks which characterise the multiple shale detachment zones in the area. Here we apply both the Fry Method of finite strain analysis and illite crystallinity by X-ray diffraction analysis to examine the potential strain variations between different shear and fault domains. Shear domains show less variable and “higher-grade” illite crystallinity values, while the Fry Method results show higher strain values in these shear domains. This is confirmed by QEMSCAN mineral mapping of each domain type, where shear domains show a far more developed tectonic fabric, indicating a much higher degree of strain is accommodated continually throughout these relatively thin shear zones. The fault domains they delineate, by contrast, show far less internal strain, which is accommodated discontinuously by discrete, low-offset, fault planes. Data from our results also show a remarkably strong correlation between illite crystallinity and finite strain, and while the small number of samples involved in this study leads us to caution the over-interpretation of these results, it points to a strong relationship between illite crystallinity and finite strain at low temperatures. If further investigated and quantified, this relationship could provide a powerful and inexpensive tool for strain determination in fine-grained rocks.